Prions : current progress in advanced research - Sakudo, Akikazu; Onodera, Takashi (Caister Academic Press, 2019)
The book opens with an introductory chapter that provides an overview. This is followed by four chapters (chapters 2-5) dealing with fundamental aspects of prion biology, including functions of the cellular isoform of prion protein (PrPC) and molecular mechanisms of prion diseases. The next two chapters (chapters 6-7) focus on clinical aspects of human prion diseases and current approaches for effective inactivation methods. The last part of the book (chapters 8-9) summarizes animal prion diseases, including BSE, scrapie and chronic wasting disease (CWD). In the final chapter, Professor Onoder.